PENGARUH KEBERHASILAN WEBSITE VISUAL APPEAL TERHADAP CUSTOMER SATISFACTION DAN REPURCHASE INTENTION PADA UNIQLO DI INDONESIA - Pranabowo, Hendy; Secapramana, Laurentia Verina Halim (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
According to the ministry of industry, Agung Gumiwang said that the textile and apparel industry is one of the priority sectors in the Indonesia 4.0 marketing program which is important to develop, where in 2020 the export performance of textiles and clothing in 2020 reached 10.62 billion and contributed to the gross domestic product of non-oil and gas processing of 6.76% (Kontan.co.id, 2021). Research on intention to use m-commerce apparel is important because consumers have received stimulus from products that have been seen by individuals, so this will cause individual anxiety to use the product and will cause anxiety to make purchases. Customer retention affects the continuity of business relationships between customers and companies from either services or products. This research uses Uniqlo website user objects in Indonesia, this research is a modification of Chi's research model (2018) which has the variables of website visual appeal, clothing visual appeal, website information quality, web response time, web security, brand trust, satisfaction and intention to use clothing and the research model from Mahmoud (2018) uses conflict handling and customer retention variables. The research model uses SEM and AMOS software, the results of the study show that all hypotheses are positively supported.